Effect of Dexamethasone as an Additive to Ropivacaine on Duration of Ultrasound Guided Transversus Abdominis Plane Block in Cesarean Section under Spinal Anesthesia - A, Pokhrel; G, Kafle; K, Khanal; K, Pyakurel; D, Poudel; A, Jha (Birat Journal of Health Sciences, 2024)
Introduction: Dexamethasone is increasingly used as a new adjunct to local anesthetics for prolonging the duration of action in Transversus Abdominis Plane (TAP) block. The aim of the study was to evaluate the effect of dexamethasone as an additive to 0.25% ropivacaine in duration of TAP block in patients undergoing cesarean section. Objectives: To compare the effect of dexamethasone in transverse abdominal plane block with respect to its duration for postoperative analgesia in cesarean section under spinal anesthesia. Methodology: This prospective cross sectional study was carried out at Birat Medical College Teaching Hospital among pregnant patients with American Society of Anesthesiologists(ASA)-II physical status undergoing elective caesarean section. The sample size was calculated to be 88 (44 in each group) and sample were collected using systemic random sampling technique. The parameters that were obtained were the time to first rescue analgesia request , total analgesia consumed, Numerical Rating scale score and incidence of nausea and vomiting in first 24hr. After data collection, data were entered in a predetermined Performa and analysed with SPSS version 21. Results: Time to first rescue analgesic administration was significantly prolonged in dexamethasone group (582.2 ±139.71 min) vs (135.0 ± 34.90 min) (P<0.001). Postoperative analgesics consumption was reduced in terms of doses of tramadol (130.68±24.62 mg) vs (50±0 mg) (P <0.001). NRS score was reduced in first 3-24 h postoperatively (P<0.001). No one in dexamethasone had nausea and vomiting. Conclusion: Dexamethasone as an adjunct to ropivacaine in TAP block prolonged the duration of the block, decreased total analgesia consumption and decreased the incidence of post operative nausea and vomiting.